Dielectric levitation optical tweezers for powerful mesoscale biomanipulation - Liu, Haobing; Fu, Rongxin; Nan, Fan; Guo, Zongliang; Zhao, Menglei; Zhang, Yifan; Guo, Shutong; Li, Hang; Chen, Kangfu; Chu, Bing; Lou, Kai; Zhang, H. P.; et al. (National Academy of Sciences (NAS), 2026)
Optical tweezers (OT), a cornerstone of micromanipulation, are fundamentally constrained by substrate-induced adhesion and friction, limiting their application to mesoscale objects and fragile biological specimens where overcoming these resistive forces requires physiologically damaging laser powers. Here, we overcome this long-standing challenge by introducing dielectric levitation optical tweezers (DL-OT), a multiphysics platform that seamlessly integrates alternating-current dielectric levitation with optical traps. By using negative dielectrophoresis (n-DEP) to actively neutralize the normal force, DL-OT eliminates solid–solid contact and near-wall viscous drag. Crucially, we demonstrate the fundamental superiority of this active physical levitation over traditional passive antiadhesion coatings. This physical decoupling enables the smooth translation of large biological samples using low, biologically safe optical powers (~15 mW) rather than nonviable levels (>150 mW). The creation of this frictionless environment not only boosts the maximum manipulation speed of standard microtargets by 40% but also enables the stable optical transport of previously intractable mesoscale objects (100 to 260 μm), including microgears and shrimp eggs. By preventing photothermal damage and mechanical deformation, DL-OT demonstrates very good biocompatibility, significantly enhancing cell viability postmanipulation. Building upon these advantages, we demonstrate advanced on-chip biofabrication protocols through the targeted, high-precision assembly of multicellular spheroids and the safe transport of patient-derived organoids, followed by their success in situ culture. By transforming OT from a microscale tool into a mesoscale assembly platform, DL-OT paves the way for breakthroughs in tissue engineering, regenerative medicine, and the bottom–up assembly of living systems.
Keywords: optical tweezers; dielectric levitation; micromanipulation; organoid assembly; optical trapping; 31 Biological Sciences; 51 Physical Sciences; 3106 Industrial Biotechnology; Bioengineering; Optical Tweezers; Micromanipulation; Humans; Animals